Study of intracultivar variation among main Iranian olive cultivars using SSR markers - Noormohammadi, Zahra (Acta Biologica Szegediensis, 2009)
Three Iranian olive cultivars of Geloleh, Shengeh and Rowghani with commercial interest are distributed in 3 provinces in North of Iran. Fifty one accessions belonging to these 3 olive cultivars were screened by 13 microsatellite markers revealing high genetic variability both within and between cultivars. In total, 54 alleles were detected with a mean number of 4.2 alleles per locus. Six unique allelic patterns were observed. Heterozygosity ranged from 0.00 to 1.00 while the mean number of polymorphic information content (PIC) was 0.51. The existence of homonyms, synonyms or mislabeling as well as intracultivar polymorphism was showed by allele differences between olive accessions studied. The phenogram obtained by UPGMA clustering showed variability among as well as between cultivars.